A Quasilinear Parabolic System with Nonlocal Boundary Conditions and Localized Sources (Communications in Mathematical Research, 2021)
This paper investigates the properties of solutions to a quasilinear parabolicsystem with nonlocal boundary conditions and localized sources. Conditions for theexistence of global or blow-up solutions are given. Global blow-up property and blow-up rate estimates are also derived.
Keywords: global existence; finite time blow-up; localized source; nonlocal boundary; global blow-up; blow-up rate.